Pengembangan Profesionalisme Guru melalui Pelatihan Perancangan Aktivitas STEM bagi Guru SD/MI - Dita Aldila Krisma; Paskalia Pradanti; Siti Nurul Hidayah (Universitas Nusantara PGRI Kediri, 2026)
Efforts to develop teacher professionalism, one of which is through learning innovation, need to be carried out continuously so that teachers' knowledge, understanding and skills related to their duties are always up to date with world progress. However, there are not many learning innovations to help students master 21st century skills because teachers do not know how to plan and implement them and not all teachers attend training to find out the development of learning innovations. Therefore, this service aims to develop the understanding and readiness of elementary school (SD/ MI) teachers in designing STEM learning. The method in this service goes through stages of activities, namely literature study, preparation of training materials, strengthening of training concepts, implementation of training, evaluation of activities, and preparation of outputs. The results obtained are that teachers have gained an understanding of one of the learning innovations, namely STEM activities and teachers have designed STEM activities in groups resulting in eight STEM activity designs.